Metal Imidazole-Modified Covalent Organic Frameworks as Electrocatalysts for Alkaline Oxygen Evolution Reaction - Meng Xia; Xinxin Yu; Zhuangzhuang Wu; Yuzhen Zhao; Lijuan Feng; Qi Chen (Molecules)
Since the product contains no carbon-based substances and can be driven by non-carbon-based electricity, electrocatalytic water splitting is considered to be among the most effective strategies for alleviating the energy crisis and environmental pollution. This process helps lower greenhouse gas emissions while also supporting the shift toward renewable energy sources. The anodic oxygen evolution reaction (OER) involves a more complex multi-electron transfer process, which is the principal limiting factor in overall water splitting. Extensive research has demonstrated that the controlled design of effective electrocatalysts can address this limitation. In this study, a previously unreported covalent organic framework material (COF-IM) was synthesized via a post-synthetic modification strategy. Notably, COF-IM contains imidazole nitrogen metal active sites. Transition metal-coordinated COF-IM@Co can function as a highly effective electrocatalyst, exhibiting a lower overpotential (403.8 mV@10 mA cm−2) in alkaline electrolytes, thereby highlighting its potential for practical applications in energy conversion technologies. This study offers new perspectives on the design and synthesis of COFs, while also making substantial contributions to the advancement and application of OER electrocatalysts.